2020
DOI: 10.1186/s12889-020-09075-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of obstetric danger signs among Saudi Arabian women

Abstract: Background: In the Middle East, tremendous efforts have been made to promote both maternal and child health. However, there is little information in the literature about maternal knowledge of obstetric danger signs. Thus, this study aims to investigate Saudi Arabian women's knowledge of obstetric danger signs and their determinant factors. Methods: A community-based, cross-sectional survey was conducted in primary health care centers (PHCCs) in Riyadh City. A proportionate random sample of women who have deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
10
5
Order By: Relevance
“…Many other study findings showed a higher proportion of respondents who could mention severe vaginal bleeding as the danger sign in the intra-natal period. 16,32,34,36 However, a study conducted in Saudi Arabia, 25 Tanzania 27 and Uganda 37 showed the respondent's knowledge to be lesser than our study findings. The reason could be the perception of women that some amount of bleeding is normal during delivery.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…Many other study findings showed a higher proportion of respondents who could mention severe vaginal bleeding as the danger sign in the intra-natal period. 16,32,34,36 However, a study conducted in Saudi Arabia, 25 Tanzania 27 and Uganda 37 showed the respondent's knowledge to be lesser than our study findings. The reason could be the perception of women that some amount of bleeding is normal during delivery.…”
Section: Discussioncontrasting
confidence: 89%
“…Similar findings were observed in the study of Uganda, 36 South West Ethiopia 22 and Nigeria 13 Contrast findings were observed in many other studies conducted. 25,32,34 The low level of knowledge found in our study might reflect the health worker's behaviour that they do not focus it as a danger sign during ANC visit.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations